Molecular identification and genotyping of isolated from burn patients by PCR and ERIC-PCR - Faezeh Falah; Leili Shokoohizadeh; Maryam Adabi (SAGE Publishing, 2019)
Background: Acinetobacter baumannii is one of the most important agents of hospital infections. Rapid and accurate identification and genotyping of A. baumannii is very important, especially in burn hospitals in order to prevent the spread of related nosocomial infections and to further epidemiological studies. Material and methods: For two months, 82 A. baumannii isolates were collected from burn wound swabs of patients in a major burn hospital in Tehran. A. baumannii isolates were identified by conventional microbiological test and polymerase chain reaction (PCR) using the primers of blaOXA-51 gene, while the genetic linkage of A. baumannii isolates was investigated by enterobacterial repetitive intragenic consensus (ERIC)-PCR technique. Similarity, a cut-off of ⩾ 95% was considered for classifying the genotypes. Results: The molecular test (PCR) confirmed 97.56% of phenotypic results for the detection of A. baumannii isolates. ERIC-PCR results revealed 14 different ERIC patterns (ERIC-types) including 11 common types and three unique types. Conclusion: Our findings show that we can simply and quickly detect A. baumannii isolates by PCR using blaOXA genes and genetic diversity by ERIC-PCR, respectively. These rapid and simple techniques for the routine screening and identification of clinical A. baumannii isolates could be useful with epidemic potential.